Perspektywy rozwoju energetyki odnawialnej a bilans energetyczny Polski - podstawowe problemy i dylematy - Stankiewicz, Bogusław (Perspectives of Development of Renewable Energy Sources Versus the Energy Balance of Poland - Basic Issues and Dilemmas, 2009)
The renewable energy matter is still discussed and controversial in Poland. The complexity of this issue is visible not only within the same sector, but also and above all in the context of the present and perspective energy balance matter in Poland, which assumingly ought to provide power safety and therefore the sustainable development of the whole country's energy sector. In addition the inner difficulties and tension while accustoming the renewable energy sources contrive in not being able to carry out the quality changes within power engineering programme which is implemented in the EU countries as we can also face both technical and technological crisis of conventional power engineering. The fundamental dilemmas and priority of overcoming them are presented in this work - the accurate estimation of national renewable energy capability and the role of the centre as a demand creator for RES and a modus vivendi of competition in the national power trade. Against this background solving complicated and frequently not perspicuous cost-prize problems which accompany the energy production becomes the main factor which can determine the success of RES sector with its innovative and technological potential
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 40-52